Testing universality and automatic O(a) improvement in massless lattice QCD with Wilson quarks - SINT, STEFAN (Proceedings of Science, 2010)
The chirally rotated Schrodinger functional provides a test bed for universality and automatic O(a) improvement. We here report on extensive quenched simulations of lattice QCD with Wilson quarks in the massless limit. We demonstrate that, after proper tuning of a dimension 3 boundary counterterm, the expected chirally rotated boundary conditions are indeed obtained. This implies automatic O(a) improvement which we then verify in a few examples. Universality of properly renormalized correlation functions is con?rmed by comparing to the standard set-up of the Schrodinger functional. As a by-product of this study the non-singlet current renormalisation constants ZA and ZV are obtained from ratios of 2-point functions.
PUBLISHED
Keywords: QCD; lattice; Mathematics